2014
DOI: 10.1194/jlr.m051862
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates sphingolipid levels in the liver

Abstract: Journal of Lipid Research Volume 55, 20142521 the metabolic pathway ( 3 ). Ceramide undergoes anabolic reactions to generate sphingomyelin and various glycosphingolipids, or catabolic reactions, which lead to the generation of sphingosine and sphingosine-1-phosphate (S1P). Alterations in ceramide metabolism have been implicated in many pathophysiologies, including aging ( 4-6 ), neurodegeneration ( 7,8 ), metabolic diseases ( 9-15 ), cancer (16)(17)(18)(19)(20), and stress responses ( 5 ). However, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 66 publications
4
43
0
Order By: Relevance
“…It was previously observed that an increase in acid ceramidase, which is a lysosomal enzyme, resulted in elevated lysosomal density and increased levels of autophagy (40). Autophagy has been demonstrated to serve as a cellular mechanism to limit ceramide levels in the liver (41) and also occurs as a consequence of increased sphingolipid synthesis in RAW264.7 cells following TLR4 stimulation (42). In contrast to these studies, we did not detect an increase in overall ceramide synthesis but rather a shift in composition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously observed that an increase in acid ceramidase, which is a lysosomal enzyme, resulted in elevated lysosomal density and increased levels of autophagy (40). Autophagy has been demonstrated to serve as a cellular mechanism to limit ceramide levels in the liver (41) and also occurs as a consequence of increased sphingolipid synthesis in RAW264.7 cells following TLR4 stimulation (42). In contrast to these studies, we did not detect an increase in overall ceramide synthesis but rather a shift in composition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Moreover, correlations of NASH-associated CpG sites with mRNA expression of CEACAM1, SH3BP4 (encoding transferrin receptor-trafficking protein), and NAT2 also support a role for our findings relating differential DNA methylation in NASH with impaired insulin signaling/action. [41][42][43][44][45][46][47] The mechanisms that could alter DNA methylation in the insulin-resistant liver remain to be elucidated. However, these differences in methylation may be due to altered levels of enzymes responsible for adding or removing methyl groups to the genome, such as DNMTs.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive sphingolipid ceramide is increased in Atg7 knockout mouse liver [43]. Autophagy increased when sphingolipid de novo synthesis was upregulated, indicating that lipid degradation was activated to prevent excessive sphingolipid accumulation.…”
Section: Role Of Lipophagy In Disease Statesmentioning
confidence: 99%